Efficiencies of faith and secular microfinance institutions in regions of Asia, Africa, and Latin America: A two-stage dual efficiency bootstrap DEA approach - Adithya Kiran Kolloju; Michele Meoli (Economies, 2022)
Purpose: the objective is to measure the financial and social performance of 127 microfinance institutions (MFIs) and observe the effects with explanatory factors such as 'type', 'geography region', and 'secular and faith' variables. Design/methodology/approach: The time-series performance analysis of microfinance institutions is determined in two stages. In the first stage, both the social and financial efficiencies are measured with Data Envelopment Analysis (DEA) approach. The two explanatory factors along with faith and secular variables show the effect on these determined efficiencies by the second stage of the Tobit regression Random effect Model. Findings: Financial performance is greater than the social performance from the first stage analysis. When considering the explanatory variables, the social performances are not significant with religious factors. When the regression is performed in a group, the financial score is more significant with religious and other explanatory variables. Faith-based and secular-based microfinance institutions are strongly significant if the performances (efficiencies) are highly maintained. Originality/Value: faith and secular variables are identified based on the background/history information of each microfinance institution (MFI).
Keywords: 330; DEA-approach; non-parametric; Tobit; random-effect; religion; conventional; time-series; efficiency performance; microfinance; region